1993
DOI: 10.1080/10934529309375872
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to antibiotics of heavy metal‐tolerant and heavy metal‐sensitive bacterial strains

Abstract: Seventy-three bacterial isolates from polluted streams as well as 157 of their heavy metal-tolerant (HM-tolerant) derivatives were tested for their sensitivity to ampicillin, ticarcillin, gentamicin, cephalexin, sulfamethoxazole, tetracycline and colistin. Among the parent strains 19% were sensitive to all antibiotics tested and 70% were multiple resistant. The mean resistance of parent strains was 227 antibiotics per isolate. Mean resistance was increased to 2.82 for silver-, 3.32 for gold-, 3.48 for copper-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Novick (1969) and Silver et al (1976) found that bacterial resistance to some metals was determined by extrachromosomal R-factors. R-plasmids contain genes that code for metal tolerance (Ghosh et al 1997;Wnorowski 1992). Ghosh et al (1997) attempted to transfer the plasmid-mediated metal resistance in acidophilic heterotrophic strains of Alcaligenes eutrophus to Escherichia coli; however, the metalresistant genes of A. eutrophus escaped expression in E. coli.…”
Section: Tolerancementioning
confidence: 98%
“…Novick (1969) and Silver et al (1976) found that bacterial resistance to some metals was determined by extrachromosomal R-factors. R-plasmids contain genes that code for metal tolerance (Ghosh et al 1997;Wnorowski 1992). Ghosh et al (1997) attempted to transfer the plasmid-mediated metal resistance in acidophilic heterotrophic strains of Alcaligenes eutrophus to Escherichia coli; however, the metalresistant genes of A. eutrophus escaped expression in E. coli.…”
Section: Tolerancementioning
confidence: 98%
“…While antimicrobial agents have confirmed a successful way against bacterial contamination and infection, their widespread use has produced a reservoir of antimicrobial agents and MDR microorganisms. The occurrence and persistence of antimicrobial resistant bacteria in such environments as sediment ( Timoney et al , 1978 ), soil ( Trevors, 1987 ), surface water ( Bell et al , 1980 ; Wnorowski, 1993 ), municipal drinking water ( Armstrong et al , 1981 ; Calomiris et al , 1984 ; Moffie and Mouton, 1988 ) and sewage ( Altherr and Kasweck, 1982 ; Middleton and Ambrose, 2005 ; Murray et al , 1984 ; Walter and Vennes, 1985 ), is a growing public health concern.…”
Section: Introductionmentioning
confidence: 99%